Politik Hukum Hak Angket: Analisis Terhadap Celah Legislasi dalam Undang-Undang Tentang MPR, DPR, DPD, dan DPRD dalam Pelaksanaan Pemilu 2024 - Alqusri, Rieza; Makinara, Ihdi Karim; Achayar, Gamal (Prodi Tata Negara (Siyasah) IAIN Langsa, 2025)
This study analyzes the implementation of the right of inquiry (hak angket) by the Indonesian House of Representatives (DPR) as regulated in Law Number 17 of 2014 concerning the MPR, DPR, DPD, and DPRD. The main problem lies in the unclear boundaries, mechanisms, and legal consequences of the inquiry right, particularly in overseeing the 2024 general election. Although the 1945 Constitution authorizes the DPR to exercise this instrument as part of its oversight function, its effectiveness in uncovering alleged electoral irregularities remains debated. The purpose of this research is to examine the stages, legal framework, and practical challenges of the inquiry right in responding to election-related violations, and to evaluate its role in strengthening democratic accountability. This study employs a normative legal method by analyzing constitutional provisions, statutory regulations, and the DPR’s internal rules. Findings show that the inquiry process consists of submission, preliminary discussion, investigation, special hearings, report drafting, and final decision-making. In the 2024 election context, the inquiry right is directed at proving indications of fraud and mapping institutional weaknesses of election organizers, serving as an alternative oversight mechanism outside litigation. Nonetheless, unresolved issues remain, such as its legal standing vis-à-vis election bodies, undefined operational limits, lack of timeframe, weak supervisory instruments, and uncertain outcomes. The study implies that clearer regulations and stronger enforcement mechanisms are needed so that the inquiry right functions not merely as a political tool, but as an effective instrument to ensure the DPR’s oversight role and the integrity of Indonesia’s electoral democracy.